Przedstaw funkcje w postaci iloczynowej:

[tex]x^{2} + 6x = -9[/tex]
[tex]-x^{2} + 2x = x\sqrt{3} - 2x^{2} + 30[/tex]

Z góry dziękuję :)



Odpowiedź :

x²+6x = -9

x² + 6x + 9 = 0

f(x) = x² + 6x + 9

postać iloczynowa: f(x) = (x+3)²

-x² + 2x = x√3 - 2x² + 30

x² + (2-√3)x - 30 = 0

f(x) = x² + (2-√3)x - 30

Δ = (2-√3)² - 4*(-30) = 4-2√3+3 + 120 = 127 - √3

√Δ = √(127-√3)

x₁ = -2+√3 - √(127-√3) / 2

x₂ = -2+√3 + √(127-√3) / 2

postać iloczynowa: f(x) = [x-(-2+√3 - √(127-√3) / 2 )][x-(-2+√3 + √(127-√3) / 2)]